Theoretical Investigation on C11H8 Bicyclic Carbene and Allene Isomers - Roy, Tarun; Satpati, Sayon; Thimmakondu, Venkatesan S.; Ghosal, Subhas (Frontiers in Physics, 2022)
Recent studies postulate that the presence of polycyclic aromatic hydrocarbons (PAHs) in the interstellar medium (ISM) could have been formed through resonance-stabilized arylcarbene intermediates. However, identifying most of these reactive intermediates is very challenging experimentally due to their metastability and other experimental constrains. Thus, computational studies that cover the thermodynamic versus kinetic stability of various possible structures would be beneficial for successfully identifying new molecules either in the laboratory and/or in the ISM. In this paper, more than four hundred C11H8 carbene isomers have been theoretically investigated employing density functional theory (DFT). Hybrid density functionals B3LYP and ωB97XD with 6-311+G(d,p) basis set have been used for singlet electronic states, whereas, triplet spin states were optimized at the same level using an unrestricted Hartree-Fock wavefunction. Although the skeletal structures of C11H8 can be categorized into monocyclic, bicyclic, tricyclic, tetracyclic and acyclic isomers, bicyclic carbenes have shown better stability due to the presence of resonance stabilized azulenyl/naphthyl rings. In this category, some isomers (1-, 2-, 5- and 6-azulenylcarbenes and 1- and 2-naphthylcarbenes) have also been detected recently in the laboratory/ISM. Here, we have systematically investigated the energetic and spectroscopic properties of resonance stabilized 5-, 6-, 7- and 8-membered ring containing bicyclic isomers of C11H8 and the fingerprint regions of the infrared spectrum for each class of these bicyclic compounds.